Implementasi Program Gizi Oleh Dinas Kesehatan Dalam Penurunan Stunting Di Kota Pekanbaru - Fathia Arifah Suri; Geovani Meiwanda (Peneliti.net, 2023)
Currently, there are cases of stunting in several sub-districts in the city of Pekanbaru. Nutrition programs carried out by the Pekanbaru City Health Office are expected to help improve the nutrition of target groups at risk of stunting so that there is a decrease in stunting in Pekanbaru City. This study was conducted to determine the results and factors that hinder the implementation of nutrition programs by teh Health Department in Reducing Stunting in the City of Pekanbaru. The theoritical concept used is the Charles O. Jones policy implementation theory which consists of 3 indicators, namely organization, interpretation, and application. The result of this study show that the nutrition program in spesific nutrition intervention in the form ofproviding PMT to pregnant women and toddlers, providing TTD to adolescent girls and pregnant women has been implemented, but the results are not optimal enough. This can be seen from the fact that there are still cases of stunting in Pekanbaru City. Factors that hinder the implementatin of this programbare the posyandu so that the weiging rate of toddlers has not reached the target, the uneved distribution odf nutrition officers owned,and cooperation in hospitals in theadvanced refferal flow of handling stunting toddlers from puskesmas.